2018
DOI: 10.1017/s0950268818002728
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of Middle East respiratory syndrome coronavirus in the Arabian Peninsula, 2012–2017

Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV) remains a notable disease and poses a significant threat to global public health. The Arabian Peninsula is considered a major global epicentre for the disease and the virus has crossed regional and continental boundaries since 2012. In this study, we focused on exploring the temporal dynamics of MERS-CoV in human populations in the Arabian Peninsula between 2012 and 2017, using publicly available data on case counts and combining two analytical methods. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…To date, limited studies investigate climate parameters as factors that could promote the MERS virus activity and transmission. Although MERS-CoV cases were reported throughout the year in Saudi Arabia, a seasonality pattern appears to be higher during certain months of the year [8]. Similar seasonality may exist in the Riyadh Region as well.…”
Section: Introductionmentioning
confidence: 82%
“…To date, limited studies investigate climate parameters as factors that could promote the MERS virus activity and transmission. Although MERS-CoV cases were reported throughout the year in Saudi Arabia, a seasonality pattern appears to be higher during certain months of the year [8]. Similar seasonality may exist in the Riyadh Region as well.…”
Section: Introductionmentioning
confidence: 82%
“…SARS-CoV was inactivated at 65 °C for 10 min [ 55 ] and by ultraviolet light (UVC) for 10 min [ 55 ]. MERS-CoV is also not very seasonal [ 56 ], is not strongly influenced by weather and transmission is more influenced by other measures [ 57 59 ], including camel-related events [ 60 ]. A case-crossover analysis of the impact of weather on primary cases of MERS in Saudi Arabia found more cases when conditions were relatively cold and dry [ 61 ].…”
Section: Coronavirus Seasonal Characteristicsmentioning
confidence: 99%
“…The epidemic progression in Makkah and Riyadh regions had been the highest in April 2014 and Eastern Province, in May 2013. A statistically significant biannual seasonality has been observed in Riyadh related to the large camel based seasonal-activities [28].…”
Section: Mers-cov Prevalence In Saudi Arabia and Other Geographical Domainsmentioning
confidence: 99%
“…Another study, evaluating time, season, space and spatiotemporal variation of MERS-CoV by Kulldorff 's spatial scan statistics has also identified that the 41.88% of infections occur during the spring season (with seasonal clusters being significant in April and May [28,29]. The first cases of MERS-CoV were reported from The United Arab Emirates, Qatar, Jordan, Oman and Kuwait however it spread to Riyadh and Eastern Provinces resulted in 80% cases of the region [30][31][32].…”
Section: Mers-cov Prevalence In Saudi Arabia and Other Geographical Domainsmentioning
confidence: 99%
See 1 more Smart Citation